Wojenna proza Wiktora Astafiewa a problem nienawiści i przebaczenia - Popiel-Machnicki, Wawrzyniec (Studia Rossica Posnaniensia, 2016)
Viktor Astafyev was an outstanding Russian writer and a representative of ”village prose”. In his oeuvre, along with works on the question of “man and nature”, we may find numerous important works concerning the subject of war. Astafyev fought in WWII, which left him with some unhealed wounds. In his novels about this 'Great Patriotic War', the dominating pacifist humanism triggered the first depiction of German soldiers through the prism of Christian mercy in Russian literature. The attempt to analyze the novel The Cursed and the Slain is very relevant in light of our present reality, full of news of new military conflicts, including that in eastern Ukraine.